Novel MDM2 Inhibitor XR-2 Exerts Potent Anti-Tumor Efficacy and Overcomes Enzalutamide Resistance in Prostate Cancer - Wu, Meng; Cui, Jingyi; Hou, Huimin; Li, Ying; Liu, Shengjie; Wan, Li; Zhang, Lili; Huang, Wei; Sun, Gaoyuan; Liu, Jingchao; Jin, Pengfei; He, Shunmin; et al. (Frontiers in Pharmacology, 2022)
Background: The inactivation of tumor-suppressor p53 plays an important role in second generation anti-androgens (SGAs) drug resistance and neuroendocrine differentiation in castration-resistant prostate cancer (CRPC). The reactivation of p53 by blocking the MDM2–p53 interaction represents an attractive therapeutic remedy in cancers with wild-type or functional p53. Whether MDM2-p53 inhibitor could overcome SGAs drug resistance in CRPC is still needed further research. Here, we investigated the anti-tumor efficacy and mechanisms of a novel MDM2-p53 inhibitor XR-2 in CRPC. Methods: To investigate the functions and mechanisms of XR-2 in prostate cancer, in vitro and in vivo biofunctional assays were performed. Western blot and qRT-PCR assay were performed to detect the protein and mRNA expression levels of indicated genes. CCK8, colony formation, flow cytometry and senescence assay were performed for cell function identifications. RNA-sequencing and bioinformatics analysis were mainly used to identify the influence of XR-2 on prostate cancer cells transcriptome. Subcutaneous 22Rv1 derived xenografts mice model was used to investigate the in vivo anti-tumor activity of XR-2. In addition, the broad-spectrum anti-tumor activities in vivo of XR-2 were evaluated by different xenografts mice models. Results: XR-2 could directly bind to MDM2, potently reactivate the p53 pathway and thus induce cell cycle arrest and apoptosis in wild-type p53 CRPC cell lines. XR-2 also suppresses the AR pathway as p53 regulates AR transcription inhibition and MDM2 participates in AR degradation. As a result, XR-2 efficiently inhibited CRPC cell viability, showed a synergistic effect with enzalutamide and overcame enzalutamide resistance both in vitro and in vivo. Moreover, results illustrated that XR-2 possesses broad-spectrum anti-tumor activities in vivo with favourable safety. Conclusion: MDM2-p53 inhibitor (XR-2) possesses potently prostate cancer progresses inhibition activity both in vitro and in vivo. XR-2 showed a synergistic effect with enzalutamide and overcame enzalutamide resistance.